Rare Pediatric Non‐Hodgkin Lymphomas: A Report From Children's Oncology Group Study ANHL 04B1. Issue 5 (5th January 2016) - O'Suoji, Chibuzo; Welch, Jennifer J. G.; Perkins, Sherrie L.; Smith, Lynette M.; Weitzman, Sheila; Simko, Stephen J.; Galardy, Paul J.; Bollard, Catherine M.; Gross, Thomas G.; Termuhlen, Amanda M.
Abstract : Background: Non‐Hodgkin lymphoma (NHL) is a relatively common malignancy in pediatric patients; however, a small subgroup have unusual lymphoma subtypes for the pediatric population. Procedure: The Children's Oncology Group Rare and Cutaneous NHL registry's (protocol ANHL 04B1) main objectives were to determine the pathologic, biologic, and clinical features of rare and cutaneous pediatric NHL and establish a bank of centrally reviewed tissue specimens. We report the clinical data, treatment data, and outcome for rare pediatric NHL. Results: In 101 lymphomas, there is a 97.8% concordance between the reviewing study pathologists and an 87.6% concordance between the central and institutional pathology review. Samples in the specimen bank include primary tumor tissue that is snap frozen, in paraffin blocks, or H&E‐stained and unstained paraffin slides as well as blood, serum, and bone marrow. This descriptive analysis shows that children with pediatric follicular lymphoma, mucosa‐associated lymphoid tissue, nodal marginal zone lymphoma, primary cutaneous, primary central nervous system lymphoma, and subcutaneous panniculitis‐like T‐cell lymphomas have 100% survival at a median of 2 years from enrollment. There are early deaths, mostly from progressive disease, in subjects with peripheral T‐cell (not otherwise specified), NKT, and hepatosplenic T‐cell lymphomas. Conclusions: This registry provides high‐quality biologic specimens with clinical data to investigators working on the biology of these unusual pediatric diseases.